Synthesis of jaspine B regioisomers through palladium-catalyzed stereoselective tetrahydrofuran formation: Insight into the ligand recognition of sphingosine kinases. Issue 15 (12th April 2018) - Miyagawa, Takashi; Inuki, Shinsuke; Honda, Maho; Nakamura, Shinya; Nakanishi, Isao; Fujii, Nobutaka; Oishi, Shinya; Ohno, Hiroaki
Abstract: We recently reported a structure-activity relationship study of 4- epi -jaspine B derivatives toward sphingosine kinase (SphK) and identified selective inhibitors of two SphK isoforms. In this study, we designed and synthesized jaspine B regioisomers on the basis of palladium-catalyzed tetrahydrofuran formation and late-stage cross metathesis reactions to investigate the influence of the substitution position of functional groups on SphK inhibition. Evaluation of the jaspine B regioisomers SphK inhibitory activities revealed that several of these compounds exhibited comparable SphK1/2 inhibitory potency to that of 4- epi -jaspine B. Graphical abstract: